SIMULASI KINERJA GOLD CODE PADA SISTEM KOMUNIKASI DIRECT SEQUENCE SPREAD SPECTRUM (DSSS) MELALUI KANAL MULTIPATH FADING - Muhamad Zainul Halim; Nyoman Pramaita; Pande Ketut Sudiarta (Program Studi Teknik Elektro UNUD, 2021)
The communication channel cannot be separated from noise, interference and fading.To minimize mutual interference, you can use a scatter code. This research uses Gold Codewith a code length of 31. This simulation aims to determine the effect of the number of multipathcomponents on the Gold Code performance of multipath fading channels. This simulation usesdigital modulation, namely BPSK (Binary Phase Shift Keying). In the simulation of flat fadingchannel with 1 multipath component number, the results of the comparison of simulated BERwith theoretical BER are almost the same so that the simulation results can be said to be validand can be used on selective fading channels. In the simulation of frequency selective fadingchannels with variations of multipath components have different values, this happens due tointerference. In this simulation, the number of multipath 27 components that have the mostdisruptive signals results in the worst performance. In multi-user cross-correlation, it has poorperformance, seen from the cross-correlation function, where the correlation value of user 1with 2, 3 and 4 is more than 0, this value indicates the user is being interfered with by otherusers.